Екосистемні підходи до організації компенсаційних заходів щодо відшкодування збитків на місцевому рівні - Патока, І. (Економіка природокористування і сталий розвиток, 2020)
Визначено основні аспекти формування компенсаційного механізму відшкодування збитків від забруднення та деградації екосистем на місцевому рівні, важелі впливу місцевої влади та бізнесу на його впровадження, типи компенсаційних відносин в екологічній сфері. Структуризовано способи та методи компенсації відшкодування збитків від детеорації екосистем та розроблено класифікацію інструментів економічного компенсаційного механізму на різних територіальних рівнях управління. Окреслено першочергові реформи у сфері відповідальності за шкоду, завдану екосистемам, з метою формування механізму відшкодування збитків в Україні. Обґрунтовано перспективи його запровадження на місцевому рівні. The aim of the article is to introduce the up-to date approaches to the functioning of the compensation mechanism for the refund of the losses from ecosystems pollution and to elaborate proposals for its implementation in the local environmental policy. The paper identifies the main aspects of the formation of a compensation mechanism for refund of the losses from pollution and degradation of ecosystems at the local level, types of compensatory relations in the environmental sphere, levers of influence of local authorities and business on the implementation of an effective compensation mechanism. Ways and methods of compensation for the refund of the losses from the ecosystems decontamination are structured and instruments of the economic mechanism of compensation at different territorial levels of management are classified. It is proposed to take into account the configurations of reproduction processes in the territory ecosystems while introducing a compensation mechanism for the losses from their decontamination. The compensation mechanism for ecosystem decontamination losses at the local territorial level is proved to be a special type of institutional agreement as to protection and sustainable use of ecosystem services and ecosystems at the local level and adjusting the distribution of costs and benefits between different players and stakeholders mainly via economic means. The priority reforms in the sphere of liability for damage to ecosystems to form a compensation mechanism for compensation in Ukraine are outlined. Prospects for introduction of a compensation mechanism for the refund of the losses from the ecosystems decontamination at the local level are outlined. The reform of decentralization and extension of the local powers allows for the development and implementation of the regulations at the local level that would establish a procedure for the accumulation and use of compensation costs for the destroyed community ecosystems restoration. It will contribute to the receipt of significant compensatory financial resources in local budgets for communities, to be directed exclusively for the compensatory measures.